Reconsidering the importance of harvested forests for the conservation of tree-dwelling bats ... - Russo, Danilo; Cistrone, Luca; Garonna, Antonio P.; Jones, Gareth (Zenodo, 2010)
(Uploaded by Plazi for the Bat Literature Project) Intensively managed forests are often seen as of low priority to preserve forest bats. The main conservation strategy recommended, i.e. saving unmanaged ''habitat islands'' from logging to preserve some suitable habitat, detracts conservationists' attention from ameliorating conditions for bats in harvested sites. We studied the threatened bat Barbastella barbastellus, mostly roosting in snags, in two beech forests: an unmanaged forest—the main maternity site—and a nearby, periodically logged area. We compared roost availability, roost use, capture rates, food availability and movement between these areas. The managed forest had a greater canopy closure, fewer dead trees, a smaller tree diameter and trees bearing fewer cavities than the unmanaged one. These differences helped explain the larger number of bats recorded in the unmanaged forest, where the sex ratio was skewed towards females. Prey availability was similar in both areas. We radiotracked bats to ...